Born which Way? ADHD, Situational Self-Control, and Responsibility - Polaris Koi (SPRINGER, 2022)
Debates concerning whether Attention Deficit/Hyperactivity Disorder (ADHD) mitigates responsibility often involve recourse to its genetic and neurodevelopmental etiology. For such arguments, individuals with ADHD have diminished self-control, and hence do not fully satisfy the control condition for responsibility, when there is a genetic or neurodevelopmental etiology for this diminished capacity. In this article, I argue that the role of genetic and neurobiological explanations has been overstated in evaluations of responsibility. While ADHD has genetic and neurobiological causes, rather than embrace the essentialistic notion that it directly diminishes self-control and, therefore, responsibility, we ought to think of ADHD as constraining only some self-control practices. In particular, situational self-control strategies remain feasible for people with ADHD. However, not all individuals haveaccessto these strategies. I suggest a way to evaluate responsibility in terms of situational rather than agential pleas, which tracks whether the individual had access to self-control behaviors. While I restrict my discussion to ADHD, the access-based approach is also relevant for assessments of responsibility for other cases where self-control failures are at stake.